Comparative Analysis of Thai and International Tourists' Needs Toward Cultural Tourism in Songkhla Province - Jindabot, Teerasak; Rattanapan, Nattakan; Pianroj, Nontipak; Pattano, Duangtida; Bunlueng, Patcharaporn; Sattayarak, On-anong (KKBS Journal of Business Administration and Accountancy, 2024)
This research aims to investigate the exploratory factor analysis of Thai and International tourists’ needs toward cultural tourism, and to compare Thai and International tourists’ need toward cultural tourism in Songkhla province. 418 Self-administrated questionnaires were collected, and the data were analyzed using descriptive statistics, Exploratory Factor Analysis, Independent Samples t–test, and One–Way ANOVA. The results of exploratory factor analysis found six components of tourists’ need toward cultural tourism including amenities, accessibilities, attractions, activities, available package, and ancillary services. Research finding indicated occupation has significant differences between the groups of Thai and International tourists’ need in accessibilities component.